Mathematics makes me wonder - Carpio, Kristine Joy E. (Animo Repository, 2007)
This paper draws a picture of Mathematics education in the Philippines for Years 1 to 10. The factors included for this endeavor are the curriculum, the results of various national exams and the results of the studies undertaken by the International Association for the Evaluation of Educational Achievement.